Experimentally Approaching the ICU: Monitoring Outcome-Based Responses in the Two-Hit Mouse Model of Posttraumatic Sepsis - Drechsler, Susanne (Hindawi Publishing Corporation, 2011)
To simulate and monitor the evolution of posttraumatic sepsis in mice, we combined a two-hit model of trauma/hemorrhage (TH) followed by polymicrobial sepsis with repetitive blood sampling. Anesthetized mice underwent femur fracture/sublethal hemorrhage and cecal ligation and puncture (CLP) 48 h later. To monitor outcome-dependent changes in circulating cells/biomarkers, mice were sampled daily (facial vein) for 7 days and retrospectively divided into either dead (DIE) or surviving (SUR) by post-CLP day 7. Prior to CLP, AST was 3-fold higher in DIE, while all other post-TH changes were similar between groups. There was a significant post-CLP intergroup separation. In SUR, RBC and Hb were lower, platelets and neutrophils higher, and lymphocytes mixed compared to DIE. In DIE, all organ function markers except glucose (decrease) were few folds higher compared to SUR. In summary, the combination of daily monitoring with an adequate two-hit model simulates the ICU setting, allows insight into outcome-based responses, and can identify biomarkers indicative of death in the acute posttraumatic sepsis in mice.